PEMBERDAYAAN KELOMPOK MASYARAKAT: PELATIHAN PEMANFAATAN LIMBAH SEDOTAN MENJADI KERAJINAN TANGAN - Rochana Ruliyandari; Helfi Agustin; Fitriana Putri Utami; Fatma Nuraisyah; Muhammad Syamsu Hidayat (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
The purpose of this community service activity is to improve skills and increase public knowledge about plastic waste and how to use plastic which are waste that is difficult to process by soil so that it pollutes the environment into useful products, namely bags, heat retaining mats and other crafts. The methods used are counseling, training, and mentoring. The achievements obtained from service activities are groups of housewives and teenagers to be able to make and process plastic straws into various shapes with their respective creations so that they have economic value and increase household income and reduce plastic waste